Design and fabrication of innovative egg breaker and egg yolk separator machine / Muhammad Fathurrahman Muizuddin and Miqdad Khairulmaini - Muizuddin, Muhammad Fathurrahman; Khairulmaini, Miqdad (School of Mechanical Engineering, 2023)
Separating egg yolk from egg white is a crucial task in many culinary preparations, but it can be time-consuming and messy. Moreover, many kitchen gadgets available in the market for this purpose are not efficient or easy to use. The objective of this project is to design and develop an egg yolk separator machine that can easily and efficiently separate egg yolks from egg whites, making the task simple and clean for household users. The egg yolk separator machine will consist of a funnel for holding the egg, an egg breaker, a slide for separating the egg white, and a bowl for collecting the egg yolk. The machine will be powered by a power supply, and the eggshell will be deposited in a separate bin. The development process will involve designing and prototyping the machine, testing it for efficiency and usability. The resulting egg yolk separator machine will be a user-friendly and efficient kitchen gadget. The machine's design will be optimized for usability, efficiency, and affordability, making it accessible to a wide range of users. The egg yolk separator machine will be a significant innovation in the culinary industry, providing an easy-to-use and efficient tool for separating egg yolks from egg whites. The machine's affordability and accessibility will make it a useful addition to any household kitchen, simplifying culinary preparations and reducing wastage